Analysis of Socioeconomic Factors Influencing Early Marriage Among Women Aged 20–24 in the Kalimantan Archipelago - Revangga Argo Nastio Gagah Dewantara; Siti Fatimah Nurhayati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Early marriage remains one of the social problems that affects the quality of human resources and economic development in various regions of Indonesia, including the island of Kalimantan. This phenomenon is often associated with the socio-economic conditions of the community. However, empirical studies that specifically analyze the influence of macroeconomic factors on early marriage in this region are still limited. This study aims to analyze the effect of the Human Development Index (HDI), open unemployment rate, percentage of poor population, and inflation on the proportion of women aged 20–24 who were married before the age of 18 in Kalimantan Island. This research employs a quantitative approach using panel data from five provinces on Kalimantan Island during the 2018–2024 period, sourced from Statistics Indonesia (Badan Pusat Statistik). The analysis was conducted using panel data regression with the Fixed Effects Model (FEM) approach. The results indicate that the Human Development Index, open unemployment rate, and percentage of the poor population have a negative effect on early marriage. Meanwhile, inflation does not have a significant effect on early marriage. These findings suggest that improving the quality of human development and enhancing the economic conditions of society play an important role in reducing the practice of early marriage.